Streamyx advertising strategy and customer's purchase intentions / Faezah Laim - Laim, Faezah (2010)
Purpose - The purposes of this paper is to identify the impact of Streamyx advertising strategy towards the customer's purchase intentions, to identify the most influential advertising media to the customers, and also to identify the advertising message that customer search the most in Streamyx advertising.